Oral proficiency level required by english academies in El Salvador, 2012 - Urías Contreras, Ana Patricia; Abrego Rivera, Ana Marvely; Flores de Ramírez, Ana Marcela; Mira Rodríguez, Ronald Vladimir; Zepeda de Laínez, Gilma Delfina; Garay Salinas, Ricardo (San Salvador, El Salvador : Universidad de El Salvador, 2012)
For English Academies Oral English Proficiency is the main focus of attention or skill considered while hiring a new teacher. In order to evaluate, grade and rate this skill on English speakers there exist different standardized evaluation and grading scales internationally recognized. However each institution follows and implements a different evaluation method developed most of the time by the coordinators of each institution. They take into consideration standardized criteria from generalized evaluations such as TOELF and TOEIC, yet they implement their own criteria. In most of the participants institutions, an oral interview is the method used to rate Oral Proficiency of applicants.There are other factors that contribute to be employed or not. Some institutions take into account that the candidate has already graduated or is about to graduate from school, as well as previous experience or international certifications. Nevertheless, some institutions only base their decision on the results of the interview which makes the selection process easier for both coordinators and applicants. This research is a clear overview of the different evaluation methods and stages of the hiring process of the participant institutions.
Anexos.
Tesis -- (Licenciatura en Idioma Inglés, opción Enseñanza) -- Universidad de El Salvador, San Salvador, 2012
Bibliografís: hoja 88-89
Audiencia general
Keywords: Inglés -- Enseñanza; Lenguaje y lenguas -- Enseñanza; Adquisición de segundo lenguaje; Comprensión de lectura; CENIUES